2011
DOI: 10.1111/j.1469-7610.2011.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the school-based Psychosocial Structured Activities (PSSA) program on conflict-affected children in northern Uganda

Alastair Ager,
Bree Akesson,
Lindsay Stark
et al.

Abstract: General improvement in child well-being over a 12-month period suggests that recovery and reconstruction efforts in Northern Uganda following the onset of peace had a substantive impact on the lives of children. However, exposure to the PSSA program had an additional positive impact on child well-being, suggesting its value in post-conflict recovery contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 18 publications
3
121
0
Order By: Relevance
“…[7][8][9] Some studies have also tested brief educational interventions with promising results. 10,11 This study similarly found that people believed that these types of interventions were needed, as well as suggesting other types of interventions that have not been widely studied in postconflict youth.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…[7][8][9] Some studies have also tested brief educational interventions with promising results. 10,11 This study similarly found that people believed that these types of interventions were needed, as well as suggesting other types of interventions that have not been widely studied in postconflict youth.…”
Section: Discussionsupporting
confidence: 51%
“…Findings demonstrated improved school performance and resilience at 12-month follow-up compared with children who did not experience the intervention. 10 Children displaced by conflict in Sierra Leone were interviewed before and after the Rapid-Ed intervention, designed to educate and target trauma symptoms. Findings suggest intervention was helpful, but controlled trials are needed to confirm these findings.…”
Section: Assessment Of the Needs Of Vulnerable Youth Populations In Pmentioning
confidence: 99%
“…Of these, only two studies showed gains in child well-being. In a postconflict northern Uganda study of the impact of psychosocial structured activities (PSSA) on trauma symptoms, Ager et al [8] found the mental health of children aged 7-12 years (n=203) improved naturally over 12 months. PSSA involved 15 one-hour sessions over 2 weeks and included a wide range of activities such as drama, music, art, coping strategies and safety discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Children experienced cultural, recreation and sport activities during week-long summer camps, with parents encouraged to participate or observe activities. Unlike Ager et al [8], Loughry and colleagues sought to increase children's resilience by establishing a sense of normality through local and global community engagement, e.g. by focusing on safe play areas and connecting to children in other countries via the internet.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that intervention was successful in rectifying children's behavioural and emotional well-being, and was connected to heightened caregiver support. A similar programme in a post-conflict zone of Uganda, offering activities like music, art and drama has also been found to positively impact children's psychosocial wellbeing [27].…”
mentioning
confidence: 99%